An easily overlooked cause of pulmonary arterial hypertension—thiamine deficiency - Zhao, Qianqian; Li, Menglin; Chen, Lina; Qiu, Fangfang (Frontiers in Nutrition, 2025)
Thiamine deficiency (TD), also known as vitamin B1 deficiency, is an often overlooked potential cause of pulmonary arterial hypertension (PAH). It may contribute to the pathological process of PAH through the deficiency of related coenzymes, thereby inhibiting the citric acid cycle. TD can manifest in various clinical forms, including dry beriberi and Shoshin beriberi, the latter characterized by high-output heart failure and lactic acidosis, which can lead to fatal outcomes if not promptly treated. This article reviews the physiological functions of thiamine, the pathophysiological mechanisms of TD, and its relationship with PAH. It explores the hemodynamic changes and diagnostic challenges of Shoshin beriberi and highlights the potential value of thiamine supplementation therapy. Although large-scale randomized controlled trials are currently lacking, minor studies and case reports suggest that thiamine supplementation may benefit PAH patients. Future high-quality research is needed to clarify the role of thiamine in the treatment of PAH.